The Performance Study of Ultrasonic-Assisted Membrane Anaerobic System (UMAS) in Palm Oil Mill Effluent (POME) Treatment - N. F. A., Shafie; J. M., Uloi; A. M., Som; Nour, A. H.; Zulkafli, Hassan; R. M., Yunus; A., Yahya (AENSI Publishing, 2016)
The development of palm oil industry in Malaysia has turned into phenomena in which the area of plantation expands from year to year. In the meantime, rapid growth in its downstream and upstream processing activities has also caused detrimental effect to the environment. Therefore, a new technology needs to be sought to reduce the impact on environment and at the same time renewable form of energy can be generated as an alternative source for the palm oil mill. Throughout the decades, membrane bioreactors have been widely employed in POME treatment. However, its major drawback is central to membrane fouling problem. Thus, membrane cleaning is an essential part during the operation of membrane reactors since the membrane fouling is an unavoidable issue. Ultrasonic-assisted Membrane Anaerobic System (UMAS) is a promising technology through which an ultrasonic device is applied to the system so as to reduce the fouling of membrane and at the same time increase the COD removal efficiency. The UMAS operation was evaluated at HRT of 11 days. POME sample was taken from a palm oil mill in Sungai Tengi, Selangor and was evaluated in respective 1 hour and 2 hours of sonication period in order to observe their performances in terms of percentage COD removal efficiency and methane (CH4) production. From the study, overall results demonstrated that 2 hours sonication in UMAS was better in operation compared to 1 hour operation as it produced higher COD removal efficiency and methane gas production. The 2 hours sonication operation showed steady rise and higher percentage of COD removal (98.75%) as compared to 1 hour sonication operation (97.71%). The total production of CH4 gas in 2 hours sonication experiment was 32,595 mL whereas 1 hour sonication produced 15,900 mL of CH4 gas.